Trace element partitioning and boron isotope fractionation between mica and tourmaline - Klemme, Stephan; Marschall, Horst; Jacob, Dorrit E.; Prowatke, Stefan; Ludwig, Thomas (The Canadian mineralogist, 2011)
High-grade metamorphic tourmaline and white mica from the Broken Hill area, NSW, Australia, were analyzed with laser-ablation ICP-MS and ion-probe techniques to investigate the partitioning of trace elements and fractionation of boron isotopes between these two coexisting phases. The results indicate that most trace elements show partition coefficients close to one; only elements such as Zn, Sr, the light rare-earth elements La and Ce, and Th, partition preferentially into tourmaline, whereas Rb, Ba, W, Sn, and Nb and Ta are preferentially partitioned into coexisting mica. The ion-probe measurements demonstrate that boron isotopes are strongly fractionated between mica and tourmaline, with the white mica being some 10‰ lower in d11B than coexisting tourmaline, which is found to be in rather good agreement with previous measurements and predictions from theory.
First online: 09 Mar 2017
Gesehen am 19.09.2022